Development of a microbial bioinoculo with lipolytic activity for biodegradation of waste oils in household composting system - Vásquez Alarcón , Álvaro Eduardo (2020)
Domestic waste oils are inadequate disposal have beco me great pollutants to water bodies; these compounds must be degraded to nontoxic products in order to re duce their impact on the environment and also get a benefit from product decomposition. OBJECTIVE: This project seeks to break down fats by a biotechnological process, such as the composting; well adjusted and well isolated from sources with high organic oils, in order to potentiate their activity and improve the efficiency of decomposition will be added lipolytic microorganisms. METHODOLOGY: Reactivating kept by the biotech nology program and the Corporation for Biological Research (CIB) Isolation of endogenous microorganisms preestablished composting lipolytic activity, Determi nation of the lipolytic activity of endogenous isolates composting microorganisms: The following was used, part of endogenous isolated composting, tests antago nism between the selected isolates Mounting compos ting and degradation measurement domestic oils ID. RESULTS: It was evidenced that these are consistent with those reported by the authors described above. The Czapek 3% was ideal for insulation from composting, which was standardized with household waste oils in CONCLUSIONS: Three isolates, two bacteria and a fungus, with good lipolytic activity from the sample were found composting. Likewise a nonantagonistic ratio of the fungus and bacteria HR S and R. However it was found, there is a marked antagonism of Pseudomonas sp. and Trichoderma sp. compared to other isolates obtained.